2017
DOI: 10.1101/207183
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Field evidence for manipulation of mosquito host selection by the human malaria parasite,Plasmodium falciparum

Abstract: Whether the malaria parasite Plasmodium falciparum can manipulate mosquito host choice in ways that enhance parasite transmission toward humans is unknown. We assessed the influence of P. falciparum on the blood-feeding behaviour of three of its major vectors (Anopheles coluzzii, An. gambiae and An. arabiensis) in Burkina Faso. Host preference assays using odour-baited traps revealed no effect of infection on mosquito long-range anthropophily. However, the identification of the blood meal origin of mosquitoes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
0
10
0
1
Order By: Relevance
“…For instance, recent studies have shown that parasite infection increases insecticide susceptibility in mosquitoes carrying the kdr mutation (68) and that insecticide exposure reduces parasite development in resistant mosquitoes (69). In addition, malaria parasites have been shown to modify the feeding behaviour of their mosquito vectors in ways that favour their transmission (7072), but the role of insecticide resistance that could modulate this phenomenon has not been investigated yet (73). It is therefore urgent to decipher the links between insecticide exposure, resistance mechanisms and infection by P. falciparum on the host-seeking and biting behaviour of malaria vectors to better understand malaria transmission in areas where insecticidal tools for malaria prevention are implemented.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, recent studies have shown that parasite infection increases insecticide susceptibility in mosquitoes carrying the kdr mutation (68) and that insecticide exposure reduces parasite development in resistant mosquitoes (69). In addition, malaria parasites have been shown to modify the feeding behaviour of their mosquito vectors in ways that favour their transmission (7072), but the role of insecticide resistance that could modulate this phenomenon has not been investigated yet (73). It is therefore urgent to decipher the links between insecticide exposure, resistance mechanisms and infection by P. falciparum on the host-seeking and biting behaviour of malaria vectors to better understand malaria transmission in areas where insecticidal tools for malaria prevention are implemented.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that at least some changes in antennal responses to odours are malariaspecific, and can vary depending on both the mosquito species and Plasmodium species involved. In some cases, changes in behaviour may even shift the vector's host preference towards the host species that is the most suitable to the parasite's survival, as suggested in a study showing increased anthropophagy in mosquitoes infected with sporozoites of the human malaria parasite Plasmodium falciparum [95]. Interestingly, some mosquito-borne viruses such as dengue or Lacrosse virus have also been shown to modify the behaviour of several Aedes species in ways that could enhance their transmission, suggesting that manipulation of feeding behaviour might also be common beyond malaria systems [96,97].…”
Section: (A) Infection-associated Changes In Mosquito Behaviourmentioning
confidence: 99%
“…More complex outcomes could emerge if more sources of variation are added to the equation, such as genotype-by-genotype-by-environment interactions (G × G × E) or interaction with genetic variation in the parasite. Moreover, these interactions may also be relevant at the inter-species level, for instance when several species of mosquitoes, hosts and parasites coexist in the same environment [95,108,109]. Therefore, it is crucial to assess the relative contribution of each potential factor to the overall variation in attractiveness in order to identify the ones that are the most biologically important.…”
Section: Evolutionary Ecology Of Vector Biting Amentioning
confidence: 99%
“…Bis dahin sollte jeder noch zur Kenntnis nehmen, dass Sport beim Menschen zu einer Verbesserung des Microbioms führt (38) 14 "[...] the human malaria parasite P. falciparum evolved the ability to enhance transmission toward human, the appropriate host species, by increasing mosquito anthropophagy (or decreasing zoophagy) with potentially profound public health consequences" schreiben die Autoren am Ende ihrer sehr gründlichen Originalarbeit vom 21. Oktober 2017 (61).…”
Section: Veränderungen Des Darm-microbioms Wurden Mit Einer Ganzen Reunclassified